The effect of some cosolvents and surfactants on viability of cancerous cell lines - M. Hamzeloo-Moghadam; N. Taiebi; M. Mosaddegh; B. Eslami Tehrani; S. Esmaeili (Iranian Society of Pharmacognosy, 2014)
Improving the solubility of non-soluble herbal materials is an issue of interest in cell culture based experiments. Evaluating the biological activity of these materials could become possible with the aid of cosolvents/surfactants which obviously should have little or no cytotoxic activity. In the present study, the cytotoxic activity of six cosolvents/surfactants: ethanol, methanol, Tween 20 and 80, propylene glycol (PG) and poly ethylene glycol 400 (PEG) which are usually helpful in dissolving non-soluble herbal extracts, has been evaluated against HepG-2, MCF-7 and HT-29 cells by MTT assay. Among the investigated cosolvents/surfactants, Tween 20 and 80 demonstrated the highest and ethanol and methanol the lowest cytotoxicity to the evaluated cell lines, suggesting the two latter as proper aids for improving solubility in biological experiments.